A comparative study of COI and 16 S rRNA genes for DNA barcoding of cultivable carps in India. (17th September 2013) - Mohanty, Mausumee; Jayasankar, Pallipuram; Sahoo, Lakshman; Das, Paramananda
Abstract: The 5′ region of the mitochondrial DNA gene cytochrome c oxidase subunit I (COI) is the standard marker for DNA barcoding. However, 16 S rRNA has also been advocated for DNA barcoding in many animal species. Herein, we directly compare the usefulness of COI and 16 S rRNA in discriminating six cultivable carp species: Labeo rohita, Catla catla, Cirrhinus mrigala, Labeo fimbriatus, Labeo bata and Cirrhinus reba from India. Analysis of partial sequences of these two gene fragments from 171 individuals indicated close genetic relationship between Catla catla and Labeo rohita. The results of the present study indicated COI to be more useful than 16 S rRNA for DNA barcoding of Indian carps.